THE PANCREAS: A DUAL-ROLE ORGAN IN HUMAN PHYSIOLOGY A Review of Structure and Function (Ustozlar uchun, 2025)
AbstractThe pancreas is an indispensable retroperitoneal organ with a unique dual functionality, acting as both an exocrine and an endocrine gland. This comprehensive review synthesizes current knowledge on the macroscopic and microscopic anatomy of the pancreas, correlating its intricate structure with its vital physiological roles in digestion and metabolism. Macroscopically, the gland is divided into the head, neck, body, and tail, with a complex ductal system for exocrine secretion. Microscopically, the organ is a heterocrine gland composed of two distinct components: the exocrine acini and the endocrine Islets of Langerhans. The exocrine tissue produces and secretes potent digestive enzymes—including amylase, lipase, and proteases—critical for the breakdown of carbohydrates, fats, and proteins in the small intestine.